1983
DOI: 10.5636/jgg.35.733
|View full text |Cite
|
Sign up to set email alerts
|

Inversion methods applied to Dst data.

Abstract: The geomagnetic storm-time variation Dst allows information concerning the global distribution of electrical conductivity in the upper mantle to be obtained. Such storm events can be analysed for periods up to 10 days following the storm commencement. The penetration depth of the associated induced currents within the Earth is over 1000km. Global response estimates were derived from storm data analysed by MARSHALL (1980) covering the frequency range 0.07 to 2cpd. The response data were inverted to give conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…One of the earliest works [Lahiri and Price, 1939] indicated that conductivity increases rapidly with depth, and subsequent studies [e.g., Banks, 1969;Parker, 1970;Achache et al, 1981;Hobbs, 1983;Jady and Paterson, 1983;Constable, 1993], while refining this result, have not changed the form of the conductivity curve in a substantial way. It is now generally agreed that conductivity rises from about 0.01 S/m to 1 S/m between the upper mantle and a depth of about 1000 km.…”
Section: Introductionmentioning
confidence: 99%
“…One of the earliest works [Lahiri and Price, 1939] indicated that conductivity increases rapidly with depth, and subsequent studies [e.g., Banks, 1969;Parker, 1970;Achache et al, 1981;Hobbs, 1983;Jady and Paterson, 1983;Constable, 1993], while refining this result, have not changed the form of the conductivity curve in a substantial way. It is now generally agreed that conductivity rises from about 0.01 S/m to 1 S/m between the upper mantle and a depth of about 1000 km.…”
Section: Introductionmentioning
confidence: 99%